FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Venecia Lusiyanti; Herlin Tundjung Setijaningsih (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to analyze the influence of business risk, asset structure, and growth of company on capital structure with profitability as moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2018-2020. The samples were selected using purposive sampling and 18 manufacturingcompanies were acquired as valid data. Data processing techniques using multiple regression analysis assisted by software E-views version 12. The results obtained in this study are business risk has a negative and no significant effect on capital structure,asset structure has a negative and significant effect on capital structure, company growth has positive and significant effect on capital structure. Profitability strengthensthe effect of company growth on capital structure, while profitability does not moderate the effect of business risk and asset structure on capital structure. The implication of this study is the need to consider business risks and asset structure management that will optimize a company's capital structure.